Real‐time feedback and booking behavior in the hospitality industry: Moderating the balance between imperfect judgment and imperfect prescription. Issue 1 (30th June 2012) - Bendoly, Elliot
Abstract: Revenue management (RM) systems now have an established role in the hospitality industry. Nevertheless, use of the systems varies. The price points that these systems generate through the analysis of demand forecasts are, by their very nature, imperfect prescriptions. Given the risk of forecast error in certain reservation contexts, hotel agents are often given the latitude to accept rate bids below the pricing prescriptions of these systems. The frequency and extent of such deviation is dependent in large part on the judgment of reservation agents, who in turn are influenced by their perceptions of how their actions will be viewed by higher levels of management. In this study, we use a laboratory experiment to investigate how different forms of continuous performance feedback influence agent decisions. More specifically, we consider both a revenue‐focused metric as well as a metric framed around pricing‐curve adherence as the basis of two feedback mechanisms of interest. In an attempt to provide additional insight, we also monitored physiological markers of stress and arousal to determine the emotional state of subjects. The purpose is to use such observations in support of theory regarding the impact of performance measure orientation on decision making. The results suggest implications for the practical use of continuous feedback in these settings.